Quality of Life and its sociodemographic determinants: a population-based study from rural Punjab, India - Sapana Kasaudhan; Kallur Nava Saraswathy; Vineet Chaudhary (Springer, 2024)
Abstract Background Quality of Life (QoL) is an individual's subjective perception of well-being within their cultural context. While most QoL studies focus on individuals with certain health conditions, factors such as sex, marital status, education, and family structure can influence QoL beyond age and health conditions. Considering the limited studies on QoL in the general Indian population, especially from rural areas, the present study aims to explore the QoL and sociodemographic factors affecting QoL among community-dwelling adults in rural Punjab. Methods This community-based cross-sectional study was conducted among 931 individuals of both sexes (59.6% female) aged 20-75 years residing in rural areas of Mansa, Punjab, India. Sociodemographic data were collected using an interview schedule, and QoL was measured using the WHOQOL-BREF. Results The overall mean QoL score was found to be 67.44 ± 14.7. The most affected QoL was in the physical domain (mean = 60.203 ± 13.49), followed by psychological (mean = 65.67 ± 18.3), social-relationship (mean = 69.88 ± 26.43), and environmental domains (mean = 74.05 ± 20.58). Adjusted logistic regression analysis revealed female sex, advanced age (age group ≥ 60 years), illiteracy, and unmarried status to be positively associated and family size of 6-10 members to be negatively associated with poor QoL. Conclusion The study suggests that females, elderlies, illiterates, and unmarried individuals may be at a higher risk of poor QoL. Further, education and a bigger family size appear to increase subjective well-being among participants.